A chaperonin containing T‐complex polypeptide‐1 facilitates the formation of the PbWoxT1‐PbPTB3 ribonucleoprotein complex for long‐distance RNA trafficking in Pyrus betulaefolia. Issue 3 (4th March 2023) - Wang, Shengnan; Duan, Xuwei; Wang, Shengyuan; Hao, Li; Zhang, Yi; Xu, Chaoran; Yu, Yunfei; Xiang, Ling; Jiang, Feng; Heinlein, Manfred; Li, Tianzhong; Zhang, Wenna
Summary: Numerous plant endogenous mRNAs move via phloem and thus affect the growth and development of long‐distant organs. mRNAs are transported with RNA‐binding proteins forming a ribonucleoprotein complex. However, it remains elusive how such RNP complex assembles and facilitates mRNA trafficking. Protease digestion and RNA immunoprecipitation were used to investigate the RNP assembly function of the complete Chaperonin Containing T‐complex Polypeptide‐1. In situ hybridization, hairy root transformation, microprojectile bombardment, and grafting experiments demonstrate the role of CCT complex in the transport of a PbWoxT1 ‐PbPTB3 RNP complex in Pyrus betulaefolia . PbCCT5 silenced caused defective movement of GFP‐PbPTB3 and GFP‐PbWoxT1 from hairy roots to new leaves via the phloem. PbCCT5 is shown to interact with PbPTB3. PbCCT complex enhanced PbPTB3 stabilization and permitted assembly of PbWoxT1 and PbPTB3 into an RNP complex. Furthermore, silencing of individual CCT subunits inhibited the intercellular movement of GFP‐PbPTB3 and long‐distance trafficking of PbWoxT1 and PbPTB3 in grafted plants. Taken together, the CCT complex assembles PbPTB3 and PbWoxT1 into an RNP complex in the phloem in order to facilitate the long‐distance trafficking of PbWoxT1 in P. betulaefolia . This study therefore provides important insights into the mechanism of RNP complex formation and transport.